THE SCALE OF CORPORATE BANKRUPTCIES DURING THE COVID-19 PANDEMIC - Katarzyna Boratyńska (Polityki Europejskie, Finanse i Marketing)
This article presents the impact of the COVID-19 pandemic on the scale of corporate bankruptcies in Poland. The study aims to determine the changes in the number of corporate bankruptcies during the COVID-19 pandemic according to the following criteria: type of procedure, type of activity, and province/region. The methods of analysis and processing of research results include descriptive and comparative analysis, as well as synthesis and deductive inference. The results indicate that the totalnumber of corporate bankruptcies and restructuring proceedings has increased significantly during the COVID-19 pandemic. The research shows that in 2021, in comparison to the previous year, there were 65.8% more bankruptcy and restructuring proceedings, but most of them (82%) werecarried out in the form of simplified restructuring procedures for approval of the arrangement in-troduced as part of the anti-crisis shield. The basis of the study was state public aid spent to support businesses in coping with the negative economic and social consequences triggered by the COVID-19 pandemic.